Modern trends in the teaching of foreign languages - Zakirova Nargiza Djurayevna (Peerian Journals Publishing, 2024)
This article gives ideas and reflections on the process of teaching foreign languages and the role of modern trends in this process.
Keywords: Foreign language; trends; educational programs; modern technology